Energy management in a cane molasses distillery in Thailand - Mathema, Suman Bhakta; Tentscher, Wolfgang; Shrestha, Ram M.; Verink, Johan; Mohanty, B.; The Royal Netherlands Government (Bangkok : Asian Institute of Technology, 1990)
A study on the energy consumption and the energy conservation potential in a distillery (using cane molasses as raw material ) in Thailand , which have a production capacity of 36 , 400 1 pure alcohol (p .a. ) p er day is conducted. The average specific energy consumption is 12.46 MJ/l p.a. with specific energy cost of 1.27 B/l p.a. The types of energy used comprised of fuel oil, electricity , biogas and diesel oil. Potentials of the steam generating and the utilizing system are analyzed to determine energy conservation opportunities. The highest energy conservation opportunities exists in the distillation system, which consumes 80 % of the total energy . The economic evaluation of the energy conservation measures in the distillation process using the direct overhead vapor recompression is analyzed. After implementing the VRC distillation system, introducing air preheater in the boiler and increasing the boiler load, the expected specific energy consumption is 3.00 MJ/l p.a. If all the stillage would be treated anaerobically, 2.52 MJ/l p . a. could be generated by biogas based on average composition of molasses . Even after the energy conservation measures are realized in the thermal systems , a s mall deficit of about 0 .48 MJ/l p.a. would still exist for self sufficiency of energy. To utilize the biogas produced as byproduct from wastewater treatment plant, a engine generator to be operated with biogas is proposed apart from using it for steam production . To us e biogas as engine fuel , its substantial content of H2s must be reduced for which a dry desulfurization unit u sing ferrous substance is recommended. Also it is recommended to construct a biogas storage tank, maintaining a minimum storage capacity such that no gas needs to be flared any more. The expected specific saving in energy cost i s 0 .66 B/l p.a. when energy conservation measures are realized and the energy supply is managed as proposed .
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1990
Keywords: Molasses; Distilleries -- Thailand